2020
DOI: 10.1055/s-0040-1702198
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Anterior Cruciate Ligament Injuries and Patella Alta and Trochlear Dysplasia in Adults Using Magnetic Resonance Imaging

Abstract: The aim of this study was to research the associations between anterior cruciate ligament (ACL) injuries and patella alta and trochlear dysplasia in adult patients using magnetic resonance imaging (MRI). This retrospective study included 221 adult patients: 110 with acute complete noncontact ACL tears and 111 without ACL injuries who underwent knee MRI procedures between May 2016 and July 2018. After the ACL injuries were verified using the sagittal proton density images, the patellar height and patellar tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 20 publications
3
23
2
Order By: Relevance
“…In the literature, only 2 studies have examined the relationship between ACL injury and the 2 aforementioned anatomical phenomena. 1 , 18 Ntagiopoulos et al 18 reported increased prevalence of trochlear dysplasia and patella alta in patients with ACL injury relative to the incidence of femoral trochlear dysplasia and patella alta in the general population. However, there was no significant correlation between femoral trochlear dysplasia and ACL injury in adult patients.…”
mentioning
confidence: 99%
“…In the literature, only 2 studies have examined the relationship between ACL injury and the 2 aforementioned anatomical phenomena. 1 , 18 Ntagiopoulos et al 18 reported increased prevalence of trochlear dysplasia and patella alta in patients with ACL injury relative to the incidence of femoral trochlear dysplasia and patella alta in the general population. However, there was no significant correlation between femoral trochlear dysplasia and ACL injury in adult patients.…”
mentioning
confidence: 99%
“…Our findings support the theory that the surgery attempted to equalize the quadriceps moment arm and patellar tendon moment arm as it is seen in the intact knee, 2 but the quadriceps leverage remained dominant even after the surgery. The increased anterior directed force is resisted by enlarged ACL tension at higher flexion angles 19,20 as it was illustrated in Figure 10. As ACL load increases, external rotation of the tibia 3 increases (Figure 15).…”
Section: Simulation Of Squat Extension With Different Ptlsmentioning
confidence: 79%
“…In Ecamilla's work (2000), it was argued no ACL force during squatting, however several studies stated the existence of tensional force on ACL during squatting. 16,19,21 The reason of the existence of ACL load in our study might be the absence of the primary muscles that produce posterior directed force during squatting such as hamstrings and gastrocnemius. 21 On the other hand, most of these muscles are tight for children with cerebral palsy and can generate excessive posterior directed force on tibia.…”
Section: Simulation Of Squat Extension With Different Ptlsmentioning
confidence: 86%
See 2 more Smart Citations